(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Lesion at the superior orbital margin is infrequently seen on MDP bone scintigraphy, however the exactetiology cannot always be clearly explained. Here, acase is presented showing focal uptakeof MDP tracer in right supra-orbital region. Single photon emission computed tomography/computed tomography (SPECT/CT) was done to localize and characterize this undetermined lesion. Bangladesh J. Nuclear Med. 22(1): 73-75, Jan 2019